Temperature-Dependent Residue Depletion Regularities of Tiamulin in Nile Tilapia (Oreochromis niloticus) Following Multiple Oral Administrations - Cao, Cuiyv; Liu, Yongtao; Zhang, Guodong; Dong, Jing; Xu, Ning; Zhou, Shun; Yang, Yibin; Yang, Qiuhong; Ai, Xiaohui (Frontiers in Veterinary Science, 2021)
The aim of this study was to investigate the effect of different water temperatures (19, 25, and 30°C) on tissue residue depletion of tiamulin in Nile tilapia (Oreochromis niloticus) after five consecutive days of oral administration at the dose of 20 mg/kg body weight and to calculate the corresponding elimination half-life (T1/2) and withdrawal times (WTs). After oral administration at scheduled 11 time points (1, 2, 3, 5, 7, 9, 12, 15, 20, 25, and 30 days), samples of plasma and tissues (muscle plus skin, liver, kidney, and gill) were collected. Tiamulin concentration in samples were determined by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). T1/2 was calculated by the equation: T1/2 = ln2/k. WT 1.4 software was used to calculate WT. The results showed that tiamulin was widely distributed in all tissue samples with the highest concentration in liver. At three different water temperatures, the T1/2 were calculated as 2.76, 2.13, and 1.64 days in plasma, 2.71, 1.85, and 1.31 days in muscle plus skin, 2.27, 1.70, and 1.50 days in liver, 2.84, 2.32, and 1.94 day in kidney, and 3.16, 2.42, and 1.74 days in gill, respectively. At 19°C, the order of WT is kidney (11.88 days) > liver (10.41 days) > gill (10.77 days) > plasma (8.83 days) > muscle plus skin (7.14 days). The WT for tiamulin at 25°C was in the following order: kidney (8.40 days) > liver (8.21 days) > gill (8.07 days) > plasma (7.24 days) > muscle plus skin (4.05 days). At 30°C, the WT dropped and shown as follows: gill (6.99 days) > kidney (6.51 days) > liver (6.29 days) > plasma (3.27 days) > muscle plus skin (2.92 days). The present investigations indicated that increasing the temperature from 19 to 30°C shortened T1/2 and WT of tiamulin in tilapia. To ensure the safety of fish consumption, the longest WT of tissues is suggested for tiamulin in Nile tilapia at the corresponding water temperature; i.e., WTs were 12 days at 19°C, 9 days at 25°C, and 7 days at 30°C, respectively. Overall, we intended to provide a theoretical basis for tissue residue depletion kinetics of tiamulin in fish and improve our understanding of the influence of the temperature on tissue residue depletion kinetics of tiamulin in fish.